2007
DOI: 10.1016/j.amjhyper.2007.01.010
|View full text |Cite
|
Sign up to set email alerts
|

α-1 Microglobulin as a New Inflammatory Marker in Newly Diagnosed Hypertensive Patients

Abstract: Urinary A1M is independently associated with circulating acute phase proteins in patients with newly diagnosed hypertension, whereas it is closely associated with systolic but not diastolic BP. Our findings suggest that urinary alpha-1 microglobulin may reflect the overall inflammatory status in patients with newly diagnosed essential hypertension, beyond its value as a marker of renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 22 publications
1
17
0
2
Order By: Relevance
“…A1m is known to be complexed to macromolecules (immunoglobulin A, albumin, and prothrombin), as well as to be present in a free form of a monomeric protein [18]. This protein is considered to be a marker of renal insufficiency, and to reflect the overall inflammatory status in patients with arterial hypertension and normal renal function [19]. We found that spot 18 (protein AMBP) differed significantly when mutually comparing all four groups.…”
Section: Discussionmentioning
confidence: 99%
“…A1m is known to be complexed to macromolecules (immunoglobulin A, albumin, and prothrombin), as well as to be present in a free form of a monomeric protein [18]. This protein is considered to be a marker of renal insufficiency, and to reflect the overall inflammatory status in patients with arterial hypertension and normal renal function [19]. We found that spot 18 (protein AMBP) differed significantly when mutually comparing all four groups.…”
Section: Discussionmentioning
confidence: 99%
“…There is controversial evidence from a rat model that the synthesis of α 1 -microglobulin may be stimulated by IL-6 [31]. Recently, Vyssoulis et al [32 ]have found that urinary α 1 -microglobulin is independently associated with circulating acute-phase proteins in patients with newly diagnosed hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that urinary A1M may reflect the overall inflammatory status in patients with newly diagnosed hypertension, beyond its value as a marker of renal function [14]. In order to exclude the variation associated with inflammatory markers we evaluated CRP and ferritin.…”
Section: Discussionmentioning
confidence: 99%